Community Mentoring Through Efforts to Use The Waste of Cow Dung Into Biogas and Organic Fertilizer Towards Energy Independent Society - Mei Lina Fitri Kumalasari; Abdul Muhid; Funsu Andiarna (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
The majority of people in Sendang village, the sub-district of Tulungagung Regency are as dairy farmers. 90% of the people have 5-10 dairy cows. A cow can produce approximately 15 kg of dirt, therefore, five cows can produce 75 kg of dung per day. During this time cow dung has been utilized as a biogas material, but most cow farmers still throw it into the river. Even the people who already have biogas, they also throw the rest of biogas into rivers even though the remaining dirt can be used as manure. Community assistance was based on the ABCD approach. The result is that the community can make a communal biogas installation independently and utilize the rest of the waste into fertilizer.